A simple device for the evaluation of the UV radiation index - CASALE, Giuseppe Rocco; SIANI, Anna Maria; LUCARINI, Cesare; M. Catamo (Meteorological Applications, 2003)
The solar ultraviolet radiation (UV) flux density at the earth's surface depends on the incoming solar energy and the transmission properties of the atmosphere. UV radiation is strongly absorbed by ozone in the spectral range 200-310 nm, while the attenuation is increasingly weaker at longer wavelengths. Following the discovery of the Antarctic ozone bole in 1985, the risk of a possible UV increase at ground level, due to the observed stratospheric ozone depletion, has heightened the interest within the scientific community given the potentially harmful effects on terrestrial and aquatic ecosystems. Spectroradiometers, broad-band meters and dosimeters may be used for measurements of solar UV. In addition, radiation transfer models can be used to quantify UV irradiances at various times and locations, provided that the extraterrestrial solar radiation and the state of the atmosphere are known. Information about UV radiation at the earth's surface is given by the ultraviolet index UVI', which is defined as the effective integrated irradiance (280-400 nm) weighted by the erythemal action spectrum. The UV Index is widely used by many international weather services as an indicator of UV levels at the earth's surface providing public awareness of the effects of prolonged exposure to the sun's rays. The aim of this paper is to present a device capable of estimating the UV Index. This device is a compact disc, used as a sundial, and is based on modelled UV irradiances derived from the STAR radiative transfer model (System for Transfer of Atmospheric Radiation). The device was tested in an urban setting under clear sky conditions.